Pengaruh Kecepatan Pengadukan Dan Waktu Proses Deasetilasi Kitin Dari Cangkang Kepiting (Portunus Pelagicus) Terhadap Karakteristik Kitosan - Ardiansyah, M. Frendy; Drastinawati, Drastinawati; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitosan syntesized from chitin that isolated from crab shell wastes (Portunus pelagicus). Chitosan synthesized from Chitin that isolated from crab shell wastes (Portunus pelagicus) by deacetylation process. The purpose of this research tostudy the effect of the time reaction of the stirring speed in the deacetylation process. Crab Shell in the puree with a size 100 mesh. Chitin in the crab shell powder are in isolation by process deproteination and demineralization. Chitinwhich has been syntesized and then transformed into chitosan by deacetylation process with NaOH 60%, the mass ratio chitin and NaOH 60% volume 1 : 20 (w/v), at 120˚C, stirring speed 50 rpm, 100 rpm, 200 rpm, and time reaction 60 minutes,120 minutes, 180 minutes. The results showed that the degree of deacetylation and moisture content are increased during reaction time and speed stirring increasing. The Value of yield, moisture content, and degree of deacetylation respectively ranged from 53,6%-83%, 18%-70%, 36%-70%. Chitosan with the highest value of degree of deacetylation is obtained in the reaction time of 180 minutes and stirring speed of 200 rpm with the value of degree of deacetylation is 83%, the value of yield is 69%, the moisture content is 70%, and the ash content is 10,9%.Keywords: Chitin, Chitosan, Deacetylation Process, Degree of Deacetylation, Crab Shell, Characterization.